The global threat of new and reemerging infectious diseases : reconciling U.S. national security and public health policy - Brower, Jennifer, 1967-; Chalk, Peter (Monographs (Rand Corporation) ;, 2003)
This study offers a more comprehensive analysis of the security implications of the spread of infectious diseases than has been done to date. The study examines the impact of the HIV/AIDS epidemic in South Africa, highlighting this particular crisis as a graphic example of the devastating effects that infectious disease can have on virtually every aspect of a state's functioning viability. It also makes a detailed analysis of the United States, delineating the threat posed by specific diseases; assessing the effectiveness of the existing public health infrastructure; and offering specific actions that can be taken to improve the country's ability to meet this emerging challenge.